A Polish Winter - Sheils, Shane; Sheils, Paula (Ireland : Dwarfed Films, 2009)
This animated short film presents a young boy slowly making his way through a snowy landscape before encountering a strange sight: rows of abandoned cattle cars. Inquisitively, the boy investigates and inside one of the wagons he discovers a tattered doll. It is this childhood toy which spurs memories of unimaginable hatred, cruelty and suffering. "A Polish Winter" is a tribute to the children who perished in Nazi death camps during the Holocaust.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Animated films